RESSIGNIFICANDO OS ESTÁGIOS OBRIGATÓRIOS DO CURSO DE LETRAS/EAD/UFMS: OS DESAFIOS IMPOSTOS PELA PANDEMIA, AS ESTRATÉGIAS E AS POSSIBILIDADES: REFRAMING THE PRACTICUM IN DISTANCE EDUCATION LANGUAGE AND LITERATURE COURSE FROM UFMS: THE CHALLENGES IMPOSED BY THE PANDEMIC, THE STRATEGIES AND THE POSSIBILITIES (Revista Contexto & Educação, 2022)
The pandemic caused by Covid-19 enforced us to rethink and reorganize several university actions, amongst them, the continuation of the Bachelor of Education Practicums so it was possible to comply with current legislation and emergency measures adopted. In this work, we discuss the development of the Practicum activities taken place in distance education Language and Literature course, with emphasis in Portuguese and Spanish, from UFMS, during the pandemic period in order to describe and analyze the reorganization of this curricular component during emergency remote teaching (ERT), reflecting on the appraisal carried out by the students and the possible impacts of this new format on the education of these teachers. From the combination of quantitative and qualitative data generation methods, we analyze the effects of changes in this curricular component under the theoretical framework of Piconez (1994, 2004), Pimenta (2009), Santos et al. (2020), between others, as for the Practicum, and of Freire (1987), Hooks (2017) and Souza (2006), concerning teacher education. As results, we highlight the mostly positive evaluation by research participants in relation to the Practicum, their optimist expectations about their professional future, as well as the difficulties that impacted teacher education, especially in regard to professional socialization.
Keywords: Teacher education. Bachelor of education. Emergency remote teaching.